2018
DOI: 10.1074/jbc.ra117.000618
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine hydroxylase down-regulation after loss of Abelson helper integration site 1 (AHI1) promotes depression via the circadian clock pathway in mice

Abstract: (Haigang Ren) The abbreviations used were: 5-HT, serotonin; AHI1, Abelson helper integration site 1; BMAL1, brain and muscle arnt-like protein 1; CLOCK, locomotor output cycle kaput; DA, dopamine; KO, knockout; FST, forced swim test; MAOA, monoamine oxidase A; RORα, RAR-related orphan receptor alpha; NURR1, nuclear receptor-related protein 1; TH, tyrosine hydroxylase; TST, suspension test; VMB, ventral midbrain; VTA, ventral tegmental area. AbstractAbelson helper integration site 1 (AHI1) is associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…found that the levels of NE and 5-HT significantly decreased in mouse hippocampal tissues, which was consistent with the above result. TH, PAH, and TPH were found in Cytoscape to explore biomarker metabolism, and their enzyme expression was reduced in depression model rats or patients with depression (Guo et al, 2018;Scherer et al, 2018;Lu et al, 2019). This result may indicate that CUMS leads to a decrease in TH, PAH, and TPH activity and that the concentrations of synthetic catecholamine neurotransmitters, tyrosine, and phenylalanine are reduced, resulting in the symptoms of depression.…”
Section: Amino Acid Metabolism and Synthesis Of Neurotransmittersmentioning
confidence: 97%
“…found that the levels of NE and 5-HT significantly decreased in mouse hippocampal tissues, which was consistent with the above result. TH, PAH, and TPH were found in Cytoscape to explore biomarker metabolism, and their enzyme expression was reduced in depression model rats or patients with depression (Guo et al, 2018;Scherer et al, 2018;Lu et al, 2019). This result may indicate that CUMS leads to a decrease in TH, PAH, and TPH activity and that the concentrations of synthetic catecholamine neurotransmitters, tyrosine, and phenylalanine are reduced, resulting in the symptoms of depression.…”
Section: Amino Acid Metabolism and Synthesis Of Neurotransmittersmentioning
confidence: 97%
“…All animal protocols were approved by the Animal Committee of Soochow University. Mice were anesthetized and mounted in a stereotaxic apparatus (RWD Life Science Co, Shenzhen, China) that was described previously [11]. GSK4112 was dissolved in DMSO to a concentration of 40 μM and loaded into a 5-µL Hamilton syringe, which is fixed on stereotaxic apparatus.…”
Section: Immunoblot Analysis and Antibodiesmentioning
confidence: 99%
“…FLAG‐, enhanced green fluorescent protein (EGFP)‐, pDsRed‐, Myc‐ and His‐tagged DJ‐1 plasmids were previously described (Fan et al, ; Ren, Fu, Mu, Zhen, & Wang, ). PGL3‐ TH ‐luciferase plasmid was described previously (Guo et al, ). PGL3‐ TH ‐CRE (mutant) and ΔAP‐1 plasmids were obtained using wild‐type PGL3‐ TH ‐luciferase plasmid as a template by mutation polymerase chain reaction (PCR) through the primers 5′‐CGAGGCCTGGCCTTTAAG‐3′/5′‐AGACAAGCCCCTCTGGGT‐3′ and 5′‐GAGGCAGGTGCCTGCGACAGT‐3′/5′‐CCCTCCGCCCTAGACACGACA‐3′, respectively.…”
Section: Methodsmentioning
confidence: 99%